marketing communication strategies of colleges and universities based on spatial and temporal distribution of s - Wu Lingling; Yuriy Danko; Artem Artyukhov; Tetiana Dluhopolska; Iryna Markovych (Akademičnij Oglâd, 2022)
The development of marketing strategies based on temporal and spatial student’s distribution is extremely important in order to win a niche in the market of educational services. The object of the study is information about the place of origin of the Henan Institute of Science and Technology students in 2016 and 2020. The data used are provided by the Office of Academic Affairs of Henan Institute of Science and Technology, which selects identity data of students admitted and registered at the university in 2016 and 2020. The temporal and spatial distribution and spatial aggregation characteristics of the student enrolments are analyzed, as well as factors affecting the quality of the student flows, such as geographic location, total number of students per year, and publicity. The paper uses spatial data analysis (ESDA), which determines the spatial weight between districts. Global Moran’s I index was used for spatial analysis. The analysis carried out on the example of Henan province showed that the number of graduates in each city in a given year directly affects the number of university entrants (in 2020, the largest number of school graduates was recorded in the cities of Zhoukou and Nanyang, which had the highest number of university entrants). The spatial arrangement of colleges and universities is identified as the main factor influencing the recruitment of students of each educational institution. The choice of colleges and universities by applicants and their parents in China is also determined by proximity to large cities, convenient transportation, and employment opportunities. It has been established that advertising educational services of universities is also an additional factor in their popularization and attraction of students. The important achievements and characteristics of the school should be highly summarized to ensure that all the information on the school brand is spread in the whole domain in a comprehensive manner. Different media should be selected for different students from different places. Attention should be paid to the use of new media such as WeChat, Micro-blog, Tiktok etc. Also, a significant role should be given to interpersonal communication and mobilization of the enthusiasm of graduates to increase the popularity of a particular educational institution. Colleges and universities should reflect on themselves, correct in time, and actively establish a complete, effective, and dynamic evaluation mechanism for marketing, to improve marketing strategies, including through surveys of graduates, students, parents and other stakeholders of higher education.